Differential Item Functioning and Educational Risk Factors in Guatemalan Reading Assessment - Fortin Morales, Alvaro M.; van de Vijver, Fons J. R.; Poortinga, Ype H. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
We examined Differential Item Functioning (DIF) indicators across four risk factors for successful education in Guatemala (enrollment age, urban/rural area of residence, ethnicity, and gender). Given the instability often reported in DIF literature, we employed three different approaches (chi-square, Rasch, and logistic regression) and checked for their consistency in three years of third-grade reading assessment of Guatemalan pupils. We found that removal of DIF items did not influence differences in test scores found in groups having a different status on the risk factors. Findings suggest that educational risk factors act in concert in this Guatemalan population and that that at least to some degree, there is interaction between risk factors to create bias. We conclude that DIF analysis and test-writing would benefit from taking into account multiple background risk variables.